Allama Iqbal: A Thinker Poet of Islamic Renaissance - Saira Batool; Sher Ali (Journal of Islamic and Religious Studies, 2020)
The brief yet most precise introduction of Allama Muhammad Iqbal could be summarized in one sentence: “Iqbal is the thinker poet of Islamic Renaissance.” His all concepts, thoughts, and ideology emanate from Islamic renaissance. It remains a fact that the rise and regaining by Muslims and the Islamic Ummah of their lost glory, dignity, and prosperity are directly linked with the Islamic renaissance. This very ideology is precisely and abundantly reflected in the thoughts, lectures, and poetic work of Allama Iqbal. The concept of “ego” is the most significant dimension of his thoughts, wherein he throws light on the characteristics of a true Muslim or Mo’min. On the other hand, Allama, through his concept of Islamic nationhood, expounds the ideology of an exemplary Islamic state. Therefore, in the context of the Sub-continent, his concept heralds the ideology of Pakistan. Within the perspective of Islamic renaissance in our modern age, if we delve deep into his work and thoughts, we conclude that his concept of renaissance truly represents the very Islamic renaissance. Allama Iqbal’s exceptional farsightedness and intellectual eminence could well be gauged by the fact that not only did he espouse the core ideology of the Islamic renaissance but he also presented a clear and practical framework and roadmap to realize this cherished goal. This article discusses in detail the salient features of Allama’s thoughts and ideology on the concept of Islamic renaissance in the present time.